2016
DOI: 10.12688/f1000research.8265.1
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic macular edema: it is more than just VEGF

Abstract: Diabetic macular edema is a serious visual complication of diabetic retinopathy. This article reviews the history of previous and current therapies, including laser therapy, anti-vascular endothelial growth factor agents, and corticosteroids, that have been used to treat this condition. In addition, it proposes new ways to use them in combination in order to decrease treatment burden and potentially address other causes besides vascular endothelial growth factor for diabetic macular edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…Although the recently reported results from the DRCR.net Protocol T study showed substantially better visual outcomes, the DRCR.net protocols are difficult to follow in a real-life setting for clinicians in most parts of the world [21][22][23] . The pathogenesis of DME is complicated and, in addition to VEGF, also involves inflammatory cytokines and even vitreoretinal interface abnormalities [24][25][26] . Current mainstays of DME management are control of systemic factors, focal/grid laser for non-center-involving DME, anti-VEGF agents for center-involving DME, steroids, and vitrectomy [25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the recently reported results from the DRCR.net Protocol T study showed substantially better visual outcomes, the DRCR.net protocols are difficult to follow in a real-life setting for clinicians in most parts of the world [21][22][23] . The pathogenesis of DME is complicated and, in addition to VEGF, also involves inflammatory cytokines and even vitreoretinal interface abnormalities [24][25][26] . Current mainstays of DME management are control of systemic factors, focal/grid laser for non-center-involving DME, anti-VEGF agents for center-involving DME, steroids, and vitrectomy [25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of DME is complicated and, in addition to VEGF, also involves inflammatory cytokines and even vitreoretinal interface abnormalities [24][25][26] . Current mainstays of DME management are control of systemic factors, focal/grid laser for non-center-involving DME, anti-VEGF agents for center-involving DME, steroids, and vitrectomy [25][26][27] . The ability to identify early on those patients who are likely to respond poorly to long-term anti-VEGF therapy would allow more timely consideration of alternative treatment regimens that might prove more effective in optimizing visual outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…DME management can be difficult, with only around 15% of the patients achieving significant vision recovery with laser, the current standard of care [2]. A number of pharmacotherapies are now licensed for the treatment of DME in Europe, including anti-vascular endothelial growth factor agents and corticosteroid therapies [3], which are used to target vascular endothelial growth pathways and inflammatory pathways, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibiting the release of cytokines with a corticosteroid – such as dexamethasone, triamcinolone or fluocinolone – has been shown to reduce DME and rehabilitate vision in several pivotal clinical studies [3]. ILUVIEN contains the corticosteroid fluocinolone acetonide (FAc) and uses microdosingTM technology to release FAc at a daily rate of 0.2 μg for up to 3 years [5].…”
Section: Introductionmentioning
confidence: 99%
“…5,11,12 Although effective, this is limited to treating the pathology, but not the underlying biochemical changes, and results in permanent retinal scarring. 13 Intravitreal administration of corticosteroids is beneficial for some patients with DME. 14 The mechanisms of action of these agents include nonspecific anti-inflammatory properties 14 ; VEGF is the primary mediator of the breakdown in blood-retinal barrier characteristic of DME.…”
mentioning
confidence: 99%